Visual Assessment vs. Statistical Goodness of Fit Tests for Identifying Parent Population - Mari Berry; Brian Peacock; Bobbie Foote; Lawrence Leemis (Proceedings of the Human Factors and Ergonomics Society Annual Meeting, 1988)
Statistical tests are used to identify the parent distribution corresponding to a data set. A human observer looking at a histogram can also identify a probability distribution that models the parent distribution. The accuracy of a human observer was compared to the chi-square test for discrete data and the Kolmogorov-Smirnov and chi-square tests for continuous data. The human observer proved more accurate in identifying continuous distributions and the chi-square test proved to be superior in identifying discrete distributions. The effect of sample size and number of intervals in the histogram was included in the experimental design.